Antiproliferative effects of 13α/β-steroids on triple-negative MDA-MB-231 breast cancer cells: unraveling intracellular signaling without ERα - Alexander M. Scherbakov; Yury V. Kuznetsov; Margarita A. Yastrebova; Alvina I. Khamidullina; Danila V. Sorokin; Maria O. Tserfas; Inna S. Levina (Universidade de São Paulo, 2023)
Abstract This study aimed to investigate the activities of novel 20(R)-3,20-dihydroxy-19-norpregn-1,3,5(10)-trienes (kuz7 and kuz8b) of natural 13β- and epimeric 13α-series against triple-negative MDA-MB-231 breast cancer cells. High antiproliferative activity of synthesized compounds kuz8b and kuz7 against MDA-MB-231 triple-negative cancer cells was revealed. The steroid kuz7 of natural 13β-configuration was more active against MDA-MB-231 cells than the 13α-steroid kuz8b. Cell cycle analysis revealed common patterns for the action of both tested compounds. The number of cells in the subG1 phase increased in a dose-dependent manner, indicating induction of apoptosis, which was also verified by PARP cleavage. In contrast, the number of cells in the G0/G1 phase decreases with increasing compound concentration. Steroid kuz7 at micromolar concentrations reduced the expression of GLUT1, a glucose transporter. High efficacy of the combination of kuz7 with biguanide metformin was shown, and synergistic effects on MDA-MB-231 cell growth and expression of the anti-apoptotic protein Bcl-2 were revealed. According to the obtained results, including the high activity of kuz7 against triple-negative cancer cells, the detected induction of apoptosis, and the decrease in GLUT1 expression, 13β-steroid kuz7 is of interest for further preclinical studies both alone and in combination with the metabolic drug metformin.